MONEY-CREDIT POLICY AS AN OBJECT OF THE STUDY IN THE SYSTEM OF ECONOMIC SECURITY OF THE STATE - Gudzovata О. О. (The actual problems of regional economy development, 2018)
The article aims to study the theoretical and methodological principles of monetary policy as an element in the system of ensuring economic security of the state. The purpose of the article is to generalize and clarify the essential characteristics and features of the implementation of monetary policy in the system of ensuring economic security of the state. Such research methods as the system-institutional approach for revealing signs and connections of monetary policy and economic security of the state, scientific abstraction, logical approach for forming monetary policy parameters are applied. The place, tasks and role of monetary policy in the system of components of economic security of the state are grounded. In contrast to the established approaches when determining the place of monetary policy in the system of financial security, the significance of policy in the system of economic security of the state is substantiated. The results have practical significance, which consists in the possibility of their use in the planning of monetary policy of the state.